Examination of Pedagogical Content Knowledge of Pre-Service Primary School Teachers towards STEM - Kevser Sarı; Meltem Duran (Universitas Pendidikan Indonesia, 2023)
This study examines the pedagogical content knowledge of pre-service primary school teachers towards STEM. The research's study group consists of 202 pre-service primary school teachers studying at the faculty of education of two universities in the 2021-2022 academic year. The mixed method was used in the study. The survey model was used in the quantitative dimension of the study, and the case study was used in the qualitative dimension. The study's data were collected using the